Training to Perform Ankle-Brachial Index: Systematic Review and Perspectives to Improve Teaching and Learning. Issue 2 (February 2016) - Chaudru, S.; de Müllenheim, P.-Y.; Le Faucheur, A.; Kaladji, A.; Jaquinandi, V.; Mahé, G.
Abstract : Objective: To conduct a systematic review focusing on the impact of training programs on ankle-brachial index (ABI) performance by medical students, doctors and primary care providers. Lower extremity peripheral artery disease (PAD) is a highly prevalent disease affecting ∼202 million people worldwide. ABI is an essential component of medical education because of its ability to diagnose PAD, and as it is a powerful prognostic marker for overall and cardiovascular related mortality. Methods: A systematic search was conducted (up to May 2015) using Medline, Embase, and Web of Science databases. Results: Five studies have addressed the impact of a training program on ABI performance by either medical students, doctors or primary care providers. All were assigned a low GRADE system quality. The components of the training vary greatly either in substance (what was taught) or in form (duration of the training, and type of support which was used). No consistency was found in the outcome measures. Conclusion: According to this systematic review, only few studies, with a low quality rating, have addressed which training program should be performed to provide the best way of teaching how to perform ABI. Future high quality researches are required to define objectively the best training program to facilitate ABI teaching and learning.